2008
DOI: 10.1111/j.1747-7379.2007.00114.x
|View full text |Cite
|
Sign up to set email alerts
|

U.S. Deportation Policy, Family Separation, and Circular Migration

Abstract: Since the mid‐1990s the United States has enacted a series of laws that make it easier to deport noncitizens. Drawing on findings from interviews with a random sample of 300 Salvadoran deportees, we examine how family relations, ties, remittance behavior, and settlement experiences are disrupted by deportation, and how these ties influence future migration intentions. We find that a significant number of deportees were long‐term settlers in the United States. Many had established work histories and had formed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
170
2
12

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(186 citation statements)
references
References 22 publications
(32 reference statements)
2
170
2
12
Order By: Relevance
“…Hagan et al (2008) found that, in El Salvador, 95 per cent of deportees are men, three quarters were undocumented in the United States, nearly 79 per cent have family members in the United States, and their median stay in the United States had been 8 years. The study by Headley et al (2005) of Jamaican criminal deportees revealed that 28 per cent had arrived in the United States before age 16, 98.5 per cent were men, and the average time in the United States had been 12 years.…”
Section: Twenty-first Century Deportations: Gendered Racial Removalmentioning
confidence: 99%
“…Hagan et al (2008) found that, in El Salvador, 95 per cent of deportees are men, three quarters were undocumented in the United States, nearly 79 per cent have family members in the United States, and their median stay in the United States had been 8 years. The study by Headley et al (2005) of Jamaican criminal deportees revealed that 28 per cent had arrived in the United States before age 16, 98.5 per cent were men, and the average time in the United States had been 12 years.…”
Section: Twenty-first Century Deportations: Gendered Racial Removalmentioning
confidence: 99%
“…Deportation can occur at any time, from hours after arrival to many years later (Peutz 2006;Kanstroom 2007;Hagan, Eschbach and Rodriguez 2008). If the person being deported has close family in the deporting country, especially if he or she is responsible for those left behind such as children, the impulse to return is very strong.…”
Section: Transnational and Local Tiesmentioning
confidence: 99%
“…Scholars such as those just mentioned have interviewed people deported from the USA, who have families there to whom they are determined to return. Hagan, Eschbach, and Rodriguez (2008) note that whether the person deported is supporting family in the country of origin or the deporting country, deportation means their families are left without support. There is much less work done on those families in Europe who have been separated by deportation, but similar concerns and questions are raised.…”
Section: Transnational and Local Tiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Their liminality is revealed through the spaces that they occupycamps on the outskirts of urban communities, a soccer field that even the border patrol treated as part neither of the United States nor of Mexico. Deciding to Be Legal (Hagan 1994) recounts the impact of the 1986 Immigration Control and Reform Act (IRCA) on a Mayan community living in Houston. Hagan found that, over the course of this program, participants were able to challenge initially restrictive documentation requirements such that, by the program's end, many were able to "decide" to legalize, regardless of whether they officially met eligibility requirements.…”
Section: Immigrant Communities and Their Homelandsmentioning
confidence: 99%